2017
DOI: 10.1371/journal.pone.0186325
|View full text |Cite|
|
Sign up to set email alerts
|

Structural prediction of two novel human atypical SLC transporters, MFSD4A and MFSD9, and their neuroanatomical distribution in mice

Abstract: Out of the 430 known solute carriers (SLC) in humans, 30% are still orphan transporters regarding structure, distribution or function. Approximately one third of all SLCs belong to the evolutionary conserved and functionally diverse Major Facilitator Superfamily (MFS). Here, we studied the orphan proteins, MFSD4A and MFSD9, which are atypical SLCs of MFS type. Hidden Markov Models were used to identify orthologues in several vertebrates, and human MFSD4A and MFSD9 share high sequence identity with their identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The newly identified SLC and putative transporters that were included here have been found to be mostly neuronal (Perland et al, 2016(Perland et al, , 2017cCeder et al, 2017;Lekholm et al, 2017), and the staining found here was also localized to neurons in the mixed cultures used. Glucose is mainly used to provide the neurons with one highly important product, energy in the form of ATP, a task performed in the cytosol and within the mitochondria (Jonckheere et al, 2012).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The newly identified SLC and putative transporters that were included here have been found to be mostly neuronal (Perland et al, 2016(Perland et al, , 2017cCeder et al, 2017;Lekholm et al, 2017), and the staining found here was also localized to neurons in the mixed cultures used. Glucose is mainly used to provide the neurons with one highly important product, energy in the form of ATP, a task performed in the cytosol and within the mitochondria (Jonckheere et al, 2012).…”
Section: Discussionsupporting
confidence: 59%
“…Immunocytochemistry (ICC) was performed with a set of antibodies against putative SLCs that have been verified elsewhere and that provided similar immunostaining patterns between the published ICCs ( Perland et al, 2017c ) and the ICCs performed in this study. Immunocytochemistry was performed as described in Lekholm et al (2017) with antibodies for MFSD1 [SAB3500575, Sigma, ( Perland et al, 2017b )] diluted 1:50 in Supermix blocking solution, SLC60A1 [SAB1305276, Sigma, ( Perland et al, 2017c )] diluted 1:100, MFSD11 [Sc-243473, Santa-Cruz, ( Perland et al, 2016 )] diluted 1:80, MFSD14A [Ab103836, Abcam, ( Lekholm et al, 2017 )] diluted 1:100, MFSD14B [SAB2107506, Sigma, ( Lekholm et al, 2017 )] diluted 1:100, UNC93A [Ab69443, Abcam, ( Ceder et al, 2017 )] diluted 1:100 also in Supermix together with PAN diluted 1:200 (Millipore), GFAP diluted 1:200 (Abcam) and DAPI (Sigma Aldrich) diluted in PBS 1:15,000. For fluorescent quantification, images were taken using the same exposure settings for all pictures using an Olympus microscope BX53 with an Olympus DP73 camera and CellSens Dimension software.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…On BTA16, a window from 3.07 to 3.42 Mbp was associated with C18:0, where MFSD4A, SLC41A1, and SLC45A3, all solute carrier family members, are located. The MFSD4A gene was identified as a transporter expressed in food regulatory brain areas in mice (Perland et al, 2017). Those authors also suggested MFSD4A can be a sugar transporter for sharing 20% of the AA with MFSD4B, a sodium-dependent sugar transporter (Horiba et al, 2003).…”
Section: Resultsmentioning
confidence: 95%
“…Lately, several orphan transporters suggested to be putative SLCs ( Perland and Fredriksson, 2017 ; Perland et al, 2017a ) have begun to be characterized with focus on evolutionary relationship, protein structure prediction, and expression profile ( Perland et al, 2016 , 2017b , c ; Ceder et al, 2017 ; Lekholm et al, 2017 ). Previous phylogenetic analyses predicted UNC93A to be evolutionary preserved ( Ceder et al, 2017 ; Perland and Fredriksson, 2017 ; Perland et al, 2017a ), which we also confirmed.…”
Section: Discussionmentioning
confidence: 99%